Early rule-out and rule-in of myocardial infarction using sensitive cardiac Troponin I. (15th September 2015) - Druey, Sophie; Wildi, Karin; Twerenbold, Raphael; Jaeger, Cédric; Reichlin, Tobias; Haaf, Philip; Rubini Gimenez, Maria; Puelacher, Christian; Wagener, Max; Radosavac, Milos; Honegger, Ursina; Schumacher, Carmela; et al.
Abstract: Background: It is currently unknown, whether and to what extent sensitive cardiac troponin (s-cTn) allows shortening of the time required for safe rule-out and rule-in of acute myocardial infarction (AMI). Methods: We aimed to develop and validate early rule-out and rule-in algorithms for AMI using a thoroughly-examined and commonly used s-cTnI assay in a prospective multicenter study including 2173 patients presenting to the emergency department with suspected AMI. S-cTnI was measured in a blinded fashion at 0 h, 1 h, and 2 h. The final diagnosis was centrally adjudicated by two independent cardiologists. In the derivation cohort (n = 1496), we developed 1 h- and 2 h-algorithms assigning patients to "rule-out", "rule-in", or "observe". The algorithms were then prospectively validated in the validation cohort (n = 677). Results: AMI was the adjudicated diagnosis in 17% of patients. After applying the s-cTnI 1 h-algorithm developed in the derivation cohort to the validation cohort, 65% of patients were classified as "rule-out", 12% as "rule-in", and 23% to "observe". The negative predictive value for AMI in the "rule-out" group was 98.6% (95% CI, 96.9–99.5), the positive predictive value for AMI in the "rule-in" group 76.3% (95% CI, 65.4–85.1). Overall, 30-day mortality was 0.2% in the "rule-out" group, 1.0% in the "observe" group, and 3.0% in the "rule-in" group. Similar results were obtained for the 2 h-algorithm. Conclusion: When used in conjunction with other clinical information including the ECG, a simple algorithm incorporating s-cTnI values at presentation and after 1 h (or 2 h) will allow safe rule-out and accurate rule-in of AMI in the majority of patients.